Differential regulation of Shigella Spa47 ATPase activity by a native C-terminal product of Spa33 - Case, Heather B.; Gonzalez, Saul; Gustafson, Marie E.; Dickenson, Nicholas E. (Frontiers in Cellular and Infection Microbiology, 2023)
Shigella is a gram-negative bacterial pathogen that relies on a single type three secretion system (T3SS) as its primary virulence factor. The T3SS includes a highly conserved needle-like apparatus that directly injects bacterial effector proteins into host cells, subverting host cell function, initiating infection, and circumventing resulting host immune responses. Recent findings have located the T3SS ATPase Spa47 to the base of the Shigella T3SS apparatus and have correlated its catalytic function to apparatus formation, protein effector secretion, and overall pathogen virulence. This critical correlation makes Spa47 ATPase activity regulation a likely point of native control over Shigella virulence and a high interest target for non-antibiotic based therapeutics. Here, we provide a detailed characterization of the natural 11.6 kDa C-terminal translation product of the Shigella T3SS protein, Spa33, (Spa33C) showing that it is required for proper virulence and that it pulls down with several known T3SS proteins, consistent with a structural role within the sorting platform of the T3SS apparatus. In vitro binding assays and detailed kinetic analyses suggest an additional role, however, as Spa33C differentially regulates Spa47 ATPase activity based on Spa47s oligomeric state; downregulating Spa47 monomer activity and upregulating activity of both homo-oligomeric Spa47 and the hetero-oligomeric MxiN2Spa47 complex. These findings identify Spa33C as only the second known differential T3SS ATPase regulator to date, with the Shigella protein MxiN representing the other. Describing this differential regulatory protein pair begins to close an important gap in understanding of how Shigella may modulate virulence through Spa47 activity and T3SS function.